Pola Konsumsi Sayur dan Buah, Kebiasaan Olahraga dan Status Gizi Anggota Persatuan Pencak Silat Ranting Bayad Desa Bayad Tegallalang Gianyar - Sang Ayu Putu Eka Yanti; I Wayan Ambartana; Ni Made Dewantari (Jurusan Gizi, Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2018)
Antioxidants are necessary when the amount of free radicals is very excessive, excessive physical activity triggers the increase in free radicals in large numbers. Antioxidants that are coming from outside the body is found in vegetables and fruit, this research aims to know the vegetable and fruit consumption patterns, sports and nutrition status of Ranting Bayad Martial Art Unity Members at Bayad Village Tegalalang Gianyar. This research was carried out in Ranting Bayad Village, Tegallalang on April 2018 with the kind of observational research and draft cross sectional with total sample 40 people aged 11-25 years. The data collected with measurements of nutrition status of height and weight, dietary data collected using SQ-FFQ kuisioner, frequency data collected by sports interview. The results of this study the majority 97.5% of the sample have normal nutritional status. Different types of vegetable consumption 65.0% reasonably vegetable consumption, number of 92.5% less vegetable consumed and frequency of 43.5% quite a while different kinds of fruit consumption 80.0% enough fruit consumption, total 52.5% good and the frequency of eating fruit 57.5%. The frequency of 55.0% sports match. There is no tendency of linkages between different types of nutritional status with vegetable and fruit consumption, nutritional status with a number of vegetable consumption, nutritional status with the frequency of consuming vegetables and fruit, nutritional status with the frequency of sports, and there is a tendency the link between nutritional status with the amount of consumption of the fruit.Kata Kunci: Nutrition Status, Vegetable, Fruit, Sports